The Influence Of The Combination Of Palm Juice (Phoenix dactylifera) And Ringer Lactate To The Percentage Of Koi (Cyprinus rubrofuscus) Spermatozoa’s Fertility - Maheno Sri Widodo; Irfanov Hafiz; Muhammad Fadjar (Universitas Tidar, 2019)
Koi fish (Cyprinus rubrofuscus) is included in freshwater ornamental fish commodity which has high economic value. As high of the market demand, it must be balanced with the increase of Koi fish production, especially in the hatchery sector. One effort that can be done is by preserving sperm with the addition of a solution of palm juice and ringer lactate. The purpose of this study was to determine the effect of the difference and the best value of the concentration of palm juice in ringer lactate during the storage period on the fertility power of Koi Fish sperm. The research method that used is the experimental method with the main parameters of motility, viability, fertilization, hatchability, survival rate and supporting parameters of macroscopic quality of fresh sperm and water quality. The results showed that the addition of palm juice and ringer lactate gave a very real effect on the level of motility with the best value on treatment B that is equal to 50.33%, the level of viability with the best value at treatment B that is equal to 64.67%, fertilization rate with the best value at treatment B that is equal to 84,91%, hatchability level with the best value at treatment B that is equal to 69,80%, but no significant effect to survival rate of the juvenile. The function of palm juice and ringer lactate is providing energy and keep the balance of the fluid in sperm that is useful to keep sperm still alive and still moving.